TRADITION AND HARMONY: BUILDING ISLAMIC-CHRISTIAN RELATIONS THROUGH TRADITIONS IN DURENSEWU PASURUAN - Feryani Umi Rosidah (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2020)
Slametan sumber is a tradition that is carried out every year by the Durensewu Pandaan Pasuruan community, this tradition has been going on for generations. It is carried out every time at the end of the dry season by involving all elements of the Durensewu village community, both those who are Muslim or Christian, those who are young and old, unite to succeed the slametan sumber tradition. This research wants to see more broadly how this tradition acts as a field of religious harmony in the Durensewu community. In this study using a qualitative approach with interview, observation and documentation techniques as techniques for extracting data in the field. The findings of this study reveal the fact that 1). The slametan sumber tradition is one of the local cultural heritage of the Durensewu community that is routinely carried out, 2). This tradition has become one of the fields of harmony of the Durensewu community, binding a sense of social togetherness, especially Muslims and Christians who co-exist in the success of the slametan sumber tradition, 3). In the implementation of the slametan sumber tradition cannot be separated from the pros and cons of the people who agree with those who do not agree, but it does not reach deep debate.